RECYCLE PERCA BROKAT MENJADI UNFINISHED MANIPULATING FABRIC PADA BUSANA PESTA - Titin Prihatini; Filda Hatfina Haqi (Jurnal Socia Akademika, 2023)
This study aims to: 1) Know the process of recycling brocade patchwork into unfinished manipulating fabric in party clothes and 3) Know respondents' opinions about recycling brocade patchwork into unfinished manipulating fabric in party clothing. The research method used is a valid quantitative experiment with a form of factorial design. The subjects of this study were 22 respondents. Data collection using Questionnaire, Observation, and Documentation methods. Data analysis using Statistical Descriptive data analysis. The results of the study can be concluded that from the aspect of beauty can be said to be beautiful (stunning (32% and beautiful (54%) because there are still shortcomings in terms of design principles of rhythm aspects where brocade accents on the bolero and the main dress are not in Harmony. In the aspect of colour harmony and Harmony of bolero materials, it can be said to be harmonious (very harmonious (36% and 50%). Ornamental Harmony can be said to be harmonious (very harmonious (41% and harmonious (41%). The ornaments used in this party outfit are harmonious regarding colour and material. The total look is said to be harmonious (very harmonious (41% and harmonious (41%). This is because the colour selection on the primary material of the bolero is not appropriate